Enterprise Resource Planning Modification: A Literature Review - Mahaning Indrawaty Wijaya; Suzanna -; Diana Utomo (ComTech: Computer, Mathematics and Engineering Applications, 2021)
The current low success level of Enterprise Resource Planning (ERP) implementation stimulates the rise of research to find the critical success factor of it. One of the challenges of ERP implementation is to find a ‘fit’ between business and system requirements. It is claimed that standardizing business processes to follow the ERP system will positively impact organizations to follow the best practice process. However, there is another challenge that organization should not reengineer their business process to fit the ERP system, but rather modify or customize the ERP system to match their business process. This belief argues that standardizing business processes is not the right solution that applies to every organization since it can degrade an organization’s competitive advantages. Based on the background, the research aimed to construct a comprehensive review to succeed in implementing an ERP system, particularly on ERP modification, using a systematic literature review method. It was done by collecting and analyzing scientific publications related to ERP critical success factors with special attention to system modification. The literature review results in a comprehensive explanation of ERP modification. It includes elaborating on different types of misfit and customization to cultivate the understanding of ERP modification, a flowchart to analyze misfit to help the organization to evaluate modification requests, and critical success factors of modified ERP implementation.